ANALISIS RUMAHTANGGA PETANI DAN KETERPADUAN PASAR KOPI DI INDONESIA - Ratna Winandi (Departemen Agribisnis, FEM-IPB, 2008)
Coffee plays an important role in estate crop plantation industry in Indonesia, particularly those managed by farm households. Farm household activities in earning income or productive activities, consumption, investment, and family saving are interrelated. Therefore, decision on land area and coffee production will interrelate with the decision on other commodity productions or non agricultural business, consumption, investment, and saving. On the other hand, the decision on the coffee land area, production, consumption, and export nationally are influenced by the coffee price variable in effect as well as that of the previous period and the exchange rate of Indonesian rupiah on US dollar. The coffee price in Indonesia is influenced by the coffee world price and in this case it is determined by Brazilian coffee as the reference of the world price. From the analysis on the coffee market integration, it was found that the coffee market price in Indonesia integrated with the price of Brazilian coffee has a high level integration (IMC < 1).